Development of fraction domino card media: Validity and practicality for fourth-grade mathematics learning - Kharimah, Asma’ul; Fitrhriyah, Musa’adatul; Hadiyani, Vino Putra (STAI Auliaurrasyidin Tembilahan, 2025)
The prevalent use of monotonous learning media in elementary mathematics, particularly for difficult topics like fractions, often leads to low student engagement and suboptimal understanding. Game-based learning media, such as domino cards, offer a potential solution by transforming abstract concepts into interactive activities. This study aimed to develop and evaluate the validity and practicality of domino card media for teaching fractions to fourth-grade students. The research followed the Research and Development (R&D) method using the Borg and Gall model. The product underwent a systematic process including expert validation (linguist, media specialist, material expert) and attractiveness testing through individual, small-group, and field trials. The results demonstrated that the domino card media was highly valid, with validation scores of 95% (linguistic), 80% (media), and 85% (material), and highly attractive to students, with trial scores of 96.6% (individual), 94.5% (small group), and 95.7% (field). These findings indicate that the developed media is a valid, practical, and engaging tool for fraction instruction. While this study establishes a strong foundation for its use, the findings warrant further investigation through a quasi-experimental design to empirically verify its impact on student learning outcomes.